Cognitive underpinning of future thinking - De Vito, Stefania (The University of Edinburgh, 2012)
Thinking about the future can take numerous forms, varying from planning actions to foreseeing possible scenarios by means of knowledge and informed guesses, or speculations and intuitions, or imagination and creativity. Different cognitive processes are needed for each of these different types of future thinking. This thesis encompasses a series of experiments both on healthy volunteers and on brain damaged patients, revolving around the issue of “Future Thinking” (FT) that is the cognitive ability, specifically human, of envisaging one’s own future. The concept of FT and the relevant literature are presented and discussed in Chapters 2 and 3. The ability to foresee has been normally assumed to rely on the reconstructive nature of episodic memory. This hypothesis is investigated in Chapters 4, 5 and 6. In these chapters data on young adults, who mentally pre-experienced autobiographical episodes, are presented to investigate which type of cue would elicit richer visualizations and to explore possible differences between temporal and a-temporal scene construction. The findings from these experiments on healthy volunteers call for a deeper understanding of the relationship between past experience and FT. Chapter 7 discusses results revealing that aMCI patients produced fewer episodic but more semantic details for both past and future events, as compared to controls, suggesting that reminiscence and FT are the expression of the same neurocognitive system. However, contrary to what was generally thought, data on patients with Parkinson Disease with spared memory performance reported in Chapter 8 and 9 show that FT is not entirely dependent on memory (and the hippocampus), rather the results suggest that poor performance in FT is associated with poor executive control. In Chapter 10 two patients affected by dense amnesia are investigated. Chapter 11 presents a single case exhibiting florid confabulation. The results confirm that although amnesia is associated with poor performance on FT, memory deficits cannot account for the entire picture of FT deficits. Indeed, dysexecutive symptoms play an important role in eliciting FT deficits.
Keywords: future thinking; memory; executive functions